2023
DOI: 10.1002/adom.202300031
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Centrosymmetric 2D Nb3SeI7 with High In‐Plane Anisotropy and Optical Nonlinearity

Abstract: Integrating anisotropy and nonlinearity of physical properties in 2D materials is of great importance to the progress of nanoelectronic, nanophotonic, and nano‐optoelectronic applications. In this work, Nb3SeI7, a newly discovered ternary layered material with non‐centrosymmetric lattices, is introduced, which exhibits strong second harmonic generation (SHG), in‐plane anisotropic electricity, and light absorption. Symmetry breaking of 2D Nb3SeI7 induced by the polar off‐center displacement of niobium leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In contrast to the widely explored group VIB transition metal dichalcogenides, the fundamental atomic layers of a considerable portion of 2D vdWMs host in-plane anisotropy [105]. The typical members of this family include the group VA elemental semiconductors [106,107], IVA-VIA compounds [108,109], group VIII transition metal dichalcogenides [110,111], multielemental vdWMs [112][113][114], etc. Accordingly, the low-symmetry lattice structures endow these materials with anisotropic physical properties, such as the anisotropic energy dispersion, laying a solid foundation for the realization polarized devices.…”
Section: D Vdwm Polarized Photodetectorsmentioning
confidence: 99%
“…In contrast to the widely explored group VIB transition metal dichalcogenides, the fundamental atomic layers of a considerable portion of 2D vdWMs host in-plane anisotropy [105]. The typical members of this family include the group VA elemental semiconductors [106,107], IVA-VIA compounds [108,109], group VIII transition metal dichalcogenides [110,111], multielemental vdWMs [112][113][114], etc. Accordingly, the low-symmetry lattice structures endow these materials with anisotropic physical properties, such as the anisotropic energy dispersion, laying a solid foundation for the realization polarized devices.…”
Section: D Vdwm Polarized Photodetectorsmentioning
confidence: 99%
“…This method effectively lowers the metal precursor’s melting point by adsorbing and trapping evaporated molecules, ensuring a uniform distribution of the source (Figure a–c). More recently, Wang et al reported the synthesis of Nb 3 SeI 7 , a new ternary layered material via chemical vapor transport (CVT) . Nb 3 SeI 7 possesses a noncentrosymmetric lattice structure and exhibits pronounced SHG, in-plane anisotropic electrical properties, and optical absorption capabilities (Figure d–f).…”
Section: Growth Of Other Noncentrosymmetric 2d Materialsmentioning
confidence: 99%
“…219 Nb 3 SeI 7 possesses a noncentrosymmetric lattice structure and exhibits pronounced SHG, in-plane anisotropic electrical properties, and optical absorption capabilities (Figure23d−f).…”
mentioning
confidence: 99%
“…Besides, Nb 3 SeI 7 can be easily exfoliated even down to the monolayer limit, making it a promising candidate for the integration of SHG with OP dipole emission. However, the experimental demonstration of OP dipole emission in Janus Nb 3 SeI 7 and its layer-dependence has not been achieved …”
mentioning
confidence: 99%